DC-bias dependent impedance spectroscopy of BaTiO3–Bi(Zn1/2Ti1/2)O3 ceramics. Issue 9 (16th February 2016) - Kumar, Nitish; Patterson, Eric A.; Frömling, Till; Cann, David P.
Abstract : In p-type BaTiO3, a deviation from Ohm's law behavior at low fields was noted with a significant decrease in resistivity values; whereas the response of n-type Bi(Zn1/2 Ti1/2 )O3 -containing ceramics was insensitive to bias. Abstract : This report discusses the voltage-stability of the dielectric and transport properties of BaTiO3 –Bi(Zn1/2 Ti1/2 )O3 (BT–BZT) ceramics which have shown excellent properties for emerging energy applications. For p-type BaTiO3, the ceramics deviated from Ohm's law behavior at very low voltage levels along with a reversible drop in bulk resistivity by several orders of magnitude starting at bias fields as low as 0.1 kV cm −1 (∼8 V). In contrast, n-type BT–BZT ceramics exhibited a small ( i.e. less than one order of magnitude) increase in resistivity on application of small field levels. These data indicate a hole-generation mechanism which becomes active at a low voltage threshold. The bulk capacitance values calculated using AC impedance spectroscopy, however, were relatively unaffected (<15% change) by this application of a DC bias (up to ∼0.25 kV cm −1 ). These findings provide important insights into the electric transport mechanisms in BT-based ceramics.